Subtitling Techniques and the Quality of Indonesian Subtitles of The English Teacher - Hudi, Anugrah Cahyo; Hartono, Rudi; Yuliasri, Issy (Universitas Negeri Semarang, 2020)
Translation in Indonesia is not only used in literary or scientific texts, but also in an audio visual field such as a movie. Many movies in Indonesia come from other countries and use English language. In this case, movie subtitling is needed to make the audience understand the subtitles more easily. This study analyzed the subtitles of a movie called The English Teacher. This study used a descriptive qualitative method and employed documentation and questionnaire to collect data. The English and Indonesian movie scripts were distributed to Indonesian adult target readers to examine the techniques and its quality. In this study, a theory from Molina and Albir (2002) was used to analyze the techniques and the quality assessment was based on a theory from Nababan (2012). There were 12 techniques found in the subtitles. The most dominant technique used by the translator was literal. To analyze the translation quality, 18 respondents participated as the raters; 3 expert readers and 15 adults target readers. The results revealed that there were 1286 data. Based on Nababan, the maximum score of the quality was 3, while the average score of accuracy, acceptability, and readability was 2.67, 2.79, and 2.86. This study also found a relation between types of techniques employed in translation and its quality. It can be concluded that the qualities of the subtitles were accurate, acceptable, and readable.